Systemic antibacterial therapy of microbial complications of chronic dermatoses - Dzhorayeva, Svitlana; Kutasevych, Yanina; Oliinyk, Iryna; Goncharenko, Valentina; Oliinyk , Olha (Annals of Mechnikov's Institute, 2022)
Introduction. The leading principle in the treatment of people with purulent-inflammatory diseases caused by S. aureus is the rational selection and use of effective antibacterial therapy, which are based on the algorithm of differentiated prescription of complex therapy according to the nosological form of dermatosis, the nature of clinical manifestations, diagnosis and rational use of certain forms of drugs , which will make it possible to increase the effectiveness of therapy during the exacerbation period, avoid unwanted effects, reduce the systemic pharmacological load, achieve a stable, long-term remission of the disease and significantly improve the quality of life of such patientsThe aim of the work: to evaluate the antimicrobial activity of a drug containing linezolid for the treatment of microbial complications of common dermatosesMaterials & Methods: the study of the antibiotic resistance profile of 71 clinical strains of S.aureus, isolated from the affected areas of the skin of patients with chronic dermatoses, was carried out. The therapeutic efficacy of a systemic drug containing linezolid for the treatment of these diseases burdened by secondary infection has been determined. Results & Discussion: When analyzing the data on the determination of the levels of resistance of clinical strains of S. aureus, extracted from lesions, to antibacterial drugs of different chemical groups, 85.2% of penicillin-resistant strains were found, while 26.7% of them were the so-called MRSA strains, the presence of which makes it impossible to prescribe any β-lactam antibiotics to the patient. The isolated strains showed moderate resistance to tetracyclines, aminoglycosides, fluoroquinolones, and lincosamides – 47.9%, 43.7%, 31.7%, and 27.5%, respectively, and rather high resistance to macrolides – up to 62.0%. In addition, in the structure of antibiotic resistance, vancomycin-resistant strains were found - 4.2%, which indicates an increase in the aggressive potential of the pathogens obtained. Indicators of sensitivity of the extracted pathogens were the highest to drugs of oxazolidinones (sensitivity to linezolid was determined in the study) – 93.7% of strains, respectively.Evaluation of the clinical effectiveness of an antibacterial agent of systemic action containing linezolid was conducted with the participation of 30 patients with severe secondary pyoderma as a burden of chronic dermatoses. It is known from the anamnesis that in the complex therapy of these patients, antibacterial drugs of different groups were used repeatedly. When carrying out bacteriological studies of material from lesions on the skin, significant shifts in the skin biotope were established with the appearance of microorganisms with high pathogenic levels of colonization of the affected areas at the level of ≥ 106 CFU/cm2. After the complex therapy with the appointment of linezolid, according to the results of microbiological analyzes, a stable tendency to normalize the composition of the skin biotope was established.Conclusion: The data of microbiological and clinical studies allow us to recommend an antibacterial drug of systemic action containing linezolid for use at the initial stage of emergency therapy of severe forms of infectious-inflammatory complications until obtaining the result of a microbiological study with the determination of the actual antibiotic sensitivity of pathogens removed from the locus morbi of patients with chronic dermatoses. Taking into account the above data, linezolid claims a place in the standards of treatment in the first line of antibacterial drugs for systemic use. Keywords: clinical strains of S. aureus, antibiotic resistance, systemic antibiotic therapy, lynezolid.